Shared value for multinational corporations as a strategic imperative for expansion into Africa . - Magner, Ryan Victor (My University, 2014)
ABSTRACT In a socio-economic era characterised by sluggish global economic growth as well as wide-spread social challenges, businesses, governments and society at large seek ways and means to create economic value in a way that is also socially responsible. It is against this backdrop that Porter and Kramer (2011), in their ground breaking article, “The big Idea: Creating shared value”, argue that a concept they coin as “shared value”, has the ability to address the globes economic growth concerns whilst also addressing its societal challenges. The purpose of this study is to determine the extent to which Multinational Corporations based in South Africa regard shared value as a strategic imperative when expanding business operations into the African continent. In order to achieve this end, 5 top-of-mind South African based companies were studied, based on their broad African footprint, and sustained success on the African continent. Semi-structured guided interviews were then conducted with senior executives and strategy professionals at these organisations in order to ascertain the strategic concerns regarded by their organisations as imperative in nature. Content analysis was then used to extract emergent themes and outcomes from the transcribed interviews conducted. It was found that although shared value, as it is very specifically defined by Porter and Kramer (2011), was generally quite poorly understood, varying degrees of overall understanding of shared value as a whole were observed between organisations. This main finding serves as key evidence to all affected and interested parties of the possible beginnings of a paradigm shift in business thinking as it pertains to defining its role within society at large.
MBA 2014
Keywords: Social responsibility of business,International business enterprises -- Management.